The Effectiveness of Cinema Therapy in Merdeka Curriculum to Increase Elementary Students’ Learning Motivation - Hintang Susilo; Roemintoyo Roemintoyo; Sarwanto Sarwanto (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
Learning motivation is a psychological state that stimulates individuals to en-gage in the process of acquiring knowledge. The level of motivation varies amongstudents, influenced by internal factors and external factors surround-ing them. In the Merdeka curriculum, the emphasis is placed on nurturing students' interests and talents, with the teacher assuming the role of a facilita-tor. The teacher has the freedom to utilize various learning media, including the incorporation of film media, also known as cinema therapy, to enhance the learning motivation of elementary school students. This research aims to investigate the impact of learning motivation by enacting therapeutic cinema as part of the Merdeka curriculum for elementary school students. The study employed a quantitative approach through pre-experiment with one group pretest-posttest design, with elementary school students serving as the partic-ipants. Questionnaires were used as the data collection technique. This study revealed therapeutic cinema in the Merdek a curriculum increased student learning motivation. This study was evident from the comparison between the post-test questionnaire results and the pre-test questionnaire results. The use of therapeutic cinema in the Merdeka curriculum proved to be effective in enhancing the learning motivation of elementary school students.